Is There Any Benefit of Drain Placement on Postoperative Complications in Patients Undergoing the Sistrunk Procedure? - Qureshi,Talha Ahmed (2015)
Introduction Same-day, outpatient Sistrunk procedure is commonly performed to manage thyroglossal duct cyst anomalies and may lead to postoperative complications. Surgical drains are placed to prevent complications, but recent observations show no advantage and rather increased health care costs and patient discomfort. Objective The study evaluated if drain placement in the Sistrunk procedure offers any benefit on postoperative complications. Methods A retrospective analysis of patient records having undergone same-day, outpatient Sistrunk procedure from 2004 to 2014 was done. Of 58 (38 male and 20 female) patients included, 38 did not have drains placed and the remaining 20 had drains placed. Mean and median age of patients was 18.1 and 13.5 years, respectively. Postoperative complications of patients with drains versus those without drains were statistically analyzed. Results Overall, about 10% of patients had hematoma/seroma (H-S), with 6.9% of patients needing aspiration for H-S; 3.4% had wound infections; and 1.7% had pus formation. No statistically significant differences in Sistrunk-related complications between patient groups (with drain or without drain) were seen using Fisher exact (two-sided) test: H-S (p = 0.08); need for aspiration (p = 0.29); wound infection (p > 0.05); and pus formation (p = 0.35). Chi-square test also did not show any significant difference in the groups in terms of number of follow-ups. Conclusion Surgical placement of a drain in the Sistrunk procedure does not seem to offer any advantage in terms of reducing common postoperative complications. Sameday Sistrunk procedure without any drain placement may be a safer alternative without necessitating hospitalization. More studies with larger sample size are needed for further substantiation.